New high-tech venturing as process of resource accumulation - Lin, Edwin; Lin, Tom M.Y; Lin, Bou-Wen (Management decision, 2010)
Purpose - The purpose of this research is to explore, through the lens of a resource-based view and dynamic capability theory, how new ventures in high-technology industries accumulate resources to survive and sustain competitive advantage.Design methodology approach - This study used the multiple case study approach completed for three integrated circuit (IC) design companies in Taiwan by conducting in-depth interviews with senior executives in each case. Through the aforementioned case studies, the paper was able to summarize and verify the key elements and steps to find the customer and achieve the firm growth.Findings - It was found that three core elements, technology, networking and legitimacy are necessary. In addition, there are emerging and embedding steps adopted by each case in this study for new ventures to successfully penetrate the market and sustain the competitive advantage.Research limitations implications - The findings are focused on one country, and three cases of a specific industry in Taiwan. Future research can be conducted in different cultural contexts and different industries.Practical implications - New ventures in high-technology industries can follow the elements and steps suggested in this research paper to accumulate their initial resources. The strategy has been proven by the case studies therein and can be considered highly applicable.Originality value - The paper concludes that three key resources for sustaining a company's competitive advantages are necessary. Moreover, a well-orchestrated management is especially essential for new ventures in high-technology industries to succeed.